Language disorders: From neuroscience to neurorehabilitation (2011)
This manuscript has been aimed at reviewing a series of conclusive referents in neuroscience research thereby deriving a basis for intervention in neurological communication disorders. Evidence regarding recovery outcomes following alterations in neurocommunication suggests that it is difficult to predict the long-term functionality of a patient suffering a cerebral lesion. In spite of the course of recovery regarding speech and language in neurological disorders being different depending on the nature, extent and location of the lesion, some evidence suggests that around 80% of patients suffering cerebral damage have shown important improvement 10 to 22 weeks after such lesion. The recovery pattern does not allow progress to be predicted regarding time given that different types of plasticity dominate during neurological lesions' different stages. Neuroscientific evidence has pointed to the existence of variables related to neurorehabilitation and the recovery of neurocommunication alterations which are susceptible to being manipulated such as time, intensity, amount of treatment and other variables regarding intervention, as well as the neural conditions themselves. Likewise, variables have been identified as a result of neurorehabilitation related to acquisition, generalization, maintenance, interference and the effects of neurobiology supporting cognitive-linguistic behaviour.